Effectiveness of radio spokesperson's gender, vocal pitch and accent and the use of music in radio advertising - Josefa D. Martín-Santana; Clara Muela-Molina; Eva Reinares-Lara; Miriam Rodríguez-Guerra (BRQ Business Research Quarterly, 2015)
The aim of this study is to analyze how certain voice features of radio spokespersons and background music influence the advertising effectiveness of a radio spot from the cognitive, affective and conative perspectives. We used a 2222 experimental design in 16 different radio programs in which an ad hoc radio spot was inserted during advertising block. This ad changed according to combinations of spokesperson's gender (male–female), vocal pitch (low–high) and accent (local–standard). In addition to these independent factors, the effect of background music in advertisements was also tested and compared with those that only had words. 987 regular radio listeners comprised the sample that was exposed to the radio program we created. Based on the differences in the levels of effectiveness in the tested voice features, our results suggest that the choice of the voice in radio advertising is one of the most important decisions an advertiser faces. Furthermore, the findings show that the inclusion of music does not always imply greater effectiveness."
Keywords: 650; Advertising effectiveness in radio; Spokesperson's voice; Spokesperson's gender; Vocal pitch (low–high); Accent; Background music